Fluid structure interaction modelling of horizontal-axis wind turbine blades based on CFD and FEA. Issue 158 (November 2016) - Wang, Lin; Quant, Robin; Kolios, Athanasios
Abstract: The increasing size and flexibility of large wind turbine blades introduces considerable aeroelastic effects, which are caused by FSI (fluid structure interaction). These effects might result in aeroelastic instability problems, such as edgewise instability and flutter, which can be devastating to the blades and the wind turbine. Therefore, accurate FSI modelling of wind turbine blades is crucial in the development of large wind turbines. In this study, an FSI model for wind turbine blades at full scale is established. The aerodynamic loads are calculated using a CFD (computational fluid dynamics) model implemented in ANSYS FLUENT, and the blade structural responses are determined using a FEA (finite element analysis) model implemented in ANSYS Static Structural module. The interface of CFD and FEA is based on a one-way coupling, in which aerodynamic loads calculated from CFD modelling are mapped to FEA modelling as load boundary conditions. Validated by a series of benchmark computational tests, the one-way FSI model was applied to the modelling of WindPACT 1.5 MW wind turbine blade, a representative large-scale horizontal-axis wind turbine blade. Five operational conditions are assessed, with the worst case found to be near the rated wind speed. Maximum tensile/compressive stresses and tip deflections in each case are found to be within material and structural limits, according to relevant design standards. Highlights: A FSI model for horizontal-axis wind turbine blades is developed. The model is developed based on an one-way coupling of CFD and FEA. The accuracy of the model is verified by a series of benchmark calculation tests. The model has been applied to FSI modelling of WindPACT 1.5 MW wind turbine blade.